Eosinophilic Myocarditis: When Allergies Attack the Heart!. Issue 2 (March 2022) - Jain, Vardhmaan; Bansal, Agam; Aggarwal, Devika; Chetrit, Michael; Gupta, Manasvi; Bhatia, Kirtipal; Thakkar, Samarthkumar; Doshi, Rajkumar; Ghosh, Raktim; Bandopadhyay, Dhrubajyoti; Barzilai, Benico; Shiau, Carolyn Jane; et al.
Abstract : Eosinophilic myocarditis is a clinical condition whereby myocardial injury is mediated by eosinophilic infiltration. A number of underlying causes, including reactive, clonal, or idiopathic hypereosinophilic syndrome, may trigger eosinophilia. Disease presentation may vary from mild subclinical variants to fulminant myocarditis with thromboembolic complications, and in some cases, endomyocardial and valvular fibrosis may be seen. A detailed examination coupled with the use of multimodality imaging, and endomyocardial biopsy may help establish diagnosis. Treatment is aimed at symptomatic management and treating the underlying cause of eosinophilia, such as withdrawal of implicated drugs, antihelminthic therapy for infection, immunosuppression for autoimmune conditions, and targeted therapy with tyrosine kinase inhibitors in cases with clonal myeloid disorders.